Alternative Routes Between the Far East and Europe (With Special Regard to the Foreign Trade of Hungary) - Bajor, Tibor; Erdősi, Ferenc (Discussion Papers, 2013)
The growth of the weight of East Asia and Southeast Asia (hereinafter: the Far East) in the world economy seems unstoppable. For this macro-region, which is becoming the number one economic centre of the world, Europe is the second largest trade partner after North America. Due to its specific production culture and scarce natural resources, the procurement and trade sales markets of the Far East are mostly different geographically (also by continents). This short paper is only an examination of what are the natural, economic, political and logistical criteria of the goods transportation between the Far East, a region more and more appreciated in the foreign trade of Hungary and Europe on both traditional and newly created routes. For Hungary, a landlocked country, it does matter what routes can offer transportation, which is the most favourable from economic aspects and also the most reliable. In our paper, besides the analysis of infrastructure and goods flows in the Western Europe/EU/Far East relations, we also outline the possible directions and means of Hungary’s joining the trans-Eurasian land and combined (sea/land) routes.